ANALISA SIKAP DAN NORMA SUBYEKTIF MAHASISWA TERHADAP MINAT MASUK PADA UNIVERSITAS TRIDINANTI PALEMBANG - Rudy Chairuddin (Fakultas Ekonomi Universitas Tridinanti Palembang, 2014)
ABSTRACTRespondents to this study were freshman year learning 2012/2013 at the Faculty of Economics, University of tridinanti of Palembang. for the results of sampling by using equations slovin, obtained 96 samples. Based on the t-test showed that students ' attitudes affect significantly positive effectÃ‚Â Ã‚Â on the behaviour and decisions of students for studying in universities Palembang with Tridinanti. degrees of significance 0.000 < 0.05. Based on the t-test showed that subjective norms affect the behaviour of the student's decision for the interest was educated at the University of Tridinanti with Palembang. indicated a quantity value of the probability of 0,043 > 0.05. Using the test F of magnitude probability is 0.000 < 0.05 this shows that collectively the same attitudes and subjective norms of variables affect the behavior of the student's decision for the interest was educated at the University of Tridinanti. Palembang. the dominant Variables influencing the behaviour of the student's decision for the interest was educated at the University of Tridinanti. Palembang is varaiabel attitude with value magnitudes r. is 0,565504. Based on the analysis of models of Fishbein, can be concluded that students ' Attitude towards the behaviour of his decision to attended the University of Tridinanti. Palembang is positively with score 158,3. Likewise his subjective norms with regard to the quantity index 29,33. Overall decision to educated studentsÃ‚Â of Tridinanti university is positive with the number 34.83327.Keyword : Students attitude, Subjecktives norms, Behaviour of the studentÃ¢â‚¬â„¢s decition